Сultivation features of the riboflavin-producing strain Bacillus subti lis IFBG MK-1A using a bioreactor with feeding - Radchenko, M.M.; Tigunova, O.O.; Andriiash, H.S.; Shulga, S.M.; Blume, Ya.B. (Reports of the National Academy of Sciences of Ukraine, 2022)
Riboflavin plays an important role in a wide range of biological processes. The aim of the work was to establish the peculiarities of the riboflavin-producing strain Bacillus subtilis IFBG MK-1A cultivation in a bioreactor. The article shows that riboflavin accumulation for 66 hours was 13.9 g/dm3 when strain-producer was cultivated in flasks with volume of 1 dm3. Scaling of strain producer process with feeding in a bioreactor with a volume of 10 dm3 was carried out. It was established that the optimal volume of feeding was 47 %, and amount of ammonia water required for pH stabilization and riboflavin accumulation was 8 % of medium volume before inoculation. Glucose conversion was 12 %, while riboflavin accumulation — 19.1 g/dm3. It was shown that the cultivation of B. subtilis IFBG MK-1A strain using a bioreactor with periodic feeding leads to a significant increase in the accumulation of riboflavin (by 65 %) compared to the accumulation of riboflavin in flasks.